The Role of Nucleated Rbc in the Diagnosis of Neonatal Asphyxia with Meconium-Stained and Clear Amniotic Fluid - Nagi Reddy, Janga. Tarun Siva; Thiyagarajan, M.; N. E, Sudarshan. (Journal of Neonatal Surgery, 2025)
Introduction:Perinatal asphyxia remains a significant contributor to neonatal morbidity and mortality, particularly in low- and middle-income countries. Early identification of at-risk neonates is critical for initiating timely neuroprotective interventions. Nucleated red blood cells (NRBCs) and lactate levels in cord blood have emerged as promising markers of hypoxia. This study aims to evaluate the diagnostic value of NRBCs and lactate levels in neonates born through meconium-stained and clear amniotic fluid. Materials & Methods:A comparative cross-sectional study was conducted at Meenakshi Medical College Hospital and Research Institute between January and June 2024. Fifty term neonates were enrolled and divided into Group 1 (meconium-stained amniotic fluid) and Group 2 (clear amniotic fluid). Umbilical cord blood was analysed for NRBC count and lactate levels. Statistical analysis was performed using SPSS, and significance was determined at p < 0.05. Results:Group 1 neonates had significantly higher mean NRBC counts (18.63 ± 4.63) compared to Group 2 (5.87 ± 1.06; p < 0.001). Mean lactate levels were also elevated in Group 1 (5.63 ± 1.63 mmol/L) versus Group 2 (3.11 ± 0.6 mmol/L; p < 0.001). The diagnostic cut-off for NRBCs >6.5/100 WBCs showed 85% sensitivity and 95% specificity, while lactate >5.1 mmol/L demonstrated 88.9% sensitivity and 100% specificity for predicting neonatal asphyxia. Conclusion:Elevated NRBC and lactate levels in umbilical cord blood are reliable early indicators of perinatal asphyxia. Their high sensitivity and specificity make them valuable, cost-effective tools for the timely identification and management of at-risk neonates, especially in resource-limited settings.